“A suit that advantageously dress virtue” Elements for a materialist reading of anthropology in a pragmatic sense of Kant - Saldarriaga Madrigal, Andrés Eduardo (Estudios de Filosofía, 2017)
The article presents Anthropology in pragmatic sense as a work in which clearly manifests the content “material” of practical philosophy of Kant. Such content has the peculiarity of being somewhat arbitrary but essential part of practical philosophy considered as a whole, as critical and meeting system. In this respect a materialistic reading of the text proposed.